Mental health consequences caused by virtual education in the covid-19 pandemic in first-level Business Administration and Marketing students in a public university, Ecuador 2021 - Quishpe, Licy (2022)
This research was developed at Universidad de las Fuerzas Armadas Espe with students from the first semester of Business administration and Marketing. The objectives of this study were to analyze and understand the consequences of the mental health of the students because of their virtual education during the massive quarantine triggered by Covid-19. A qualitative methodology was used with a sample of 129 students to whom a survey focused on specifying detailed data of six determined aspects was applied. The results show that a little more than half of the students with 53,33% have mild symptoms of anxiety, stress and sleep problems. Therefore, it was concluded that the academic performance of the respondents was influenced by those types of symptoms. In addition, the students showed those types of symptoms because the students are not familiar with their university life as it is their first semester.